'You withhold what you are feeling so you can have a family': Latinas' perceptions on community values and postpartum depression. Issue 3 (1st July 2021) - Sampson, McClain; Yu, Miao; Mauldin, Rebecca; Mayorga, Angelina; Gonzalez, Lorena G
Abstract : Objective: The purpose of this study was to explore the postpartum depression (PPD) beliefs and experiences of mothers who access local community faith-based organisations providing family services to low-income, predominantly immigrant Latino populations. Design: Using a qualitative research design, we conducted 18 focus groups with Latina mothers to inquire about their community values and beliefs of PPD. All groups were conducted in Spanish. Setting: An academic research team located in Houston, Texas, USA, partnered with six faith-based organisations in five cities to recruit and host focus groups at the site of the organisation. Participants: One hundred and thirty-three women participated in the focus groups across all sites. Thirty-seven of them (27.8%) had given birth to a child in less than 1 year. Inclusion criteria included mothers 18 years and older and Latino ethnicity. Results: A six-step process was used to apply thematic analysis to sort data into the themes. All mothers had heard of depression after childbirth, some had experienced it and most remarked that the personal experience and community acceptance of it vary by family. The main findings suggest that mothers take pride in parenting by instilling values to support family and the value of relying on family for emotional support. Findings reveal that many mothers suffer and sacrifice for their children, they feel judged and feel they must hide their emotions. Factors such as birth and postpartum customs from a native country, gender roles and beliefs of what a good mother shape their beliefs and messages about PPD. Conclusion: Our findings indicate that programme developers should consider family and community focused education and intervention efforts to help decrease stigma and increase understanding of PPD.